Factors Influencing Provision of Basic Emergency Obstetric Care Services in Luzon, Philippines - Maria Stephanie Fay Samadan Cagayan (International Journal of Public Health Science (IJPHS), 2022)
The Basic Emergency Obstetric and Newborn Care (BEmONC) strategy was designed to provide evidence-based interventions at the primary level to control maternal and newborn mortality. With less than a decade until the conclusion of the Sustainable Development Goals, much work remains to be done in the Philippines to achieve the set target on maternal mortality. Recognition of the determinants affecting its implementation may elucidate what still needs to be addressed. This study aims to identify the facilitators and barriers to accessibility of quality BEmONC services. Eight focus group discussions consisting of BEmONC providers were conducted from February to April 2021. These were recorded, transcribed, then translated into English. Data then underwent thematic analysis using NVivo to identify emerging themes and subthemes. 102 health care providers participated in the study. Four main themes emerged: institutional capacity, service capacity, personnel capacity, and external factors. Each had its corresponding subthemes, such as infrastructure, human resources, referrals, and local government support, respectively. Factors and/or barriers to each subtheme were identified during the discussions. The study provided important insight on the factors influencing BEmONC utilization. Focal points recognized may be used by policy makers and key stakeholders to allow optimal provision of BEmONC services.